اللغة العربية في العصر الرقمي 4.0 والآثار المترتبة على تعلم اللغة العربية في المدرسة - كورنيياوان, إيدو (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
Arabic is the language of the Qur'an, which is unique in that it is a divine word directly provided by the prophet Muhammad, making the Qur'an a God-given miracle that still survives today. Arabic is superior to other languages not just because it is a religious language, but also because it has unique characteristics in terms of linguistic expertise. Approaches and methods for studying Arabic in the 4.0 era have undergone a major upheaval. The extensive integration of information and communication technology in all aspects of life, including education, characterizes the Era 4.0. Aside from that, learning Arabic in schools in the digital era is currently undergoing changes due to the use of technology in learning. This study takes the form of qualitative research, using descriptive analysis as the method of choice. According to the findings of this study, the presence of the Arabic language continues to exist in the digital era 4.0, and there is renewal in learning, followed by the urgency of learning. In current digital age, Arabic is highly vital in madarasah study. The digital era has consequences for Arabic language learning at madrasas, including the use of technology in learning, curriculum adaption, digital skill development, and the provision of Arabic language learning materials. اللغة العربية هي لغة القرآن ، وهي فريدة من نوعها من حيث أنها كلمة إلهية قدمها النبي محمد مباشرة ، مما يجعل القرآن معجزة وهبها الله ولا تزال باقية حتى اليوم. تتفوق اللغة العربية على اللغات الأخرى ليس فقط لأنها لغة دينية ، ولكن أيضا لأنها تتمتع بخصائص فريدة من حيث الخبرة اللغوية. شهدت مناهج وطرق دراسة اللغة العربية في عصر 4.0 اضطرابات كبيرة. إن التكامل الشامل لتكنولوجيا المعلومات والاتصالات في جميع جوانب الحياة ، بما في ذلك التعليم، يميز العصر 4.0. بصرف النظر عن ذلك ، فإن تعلم اللغة العربية في المدارس في العصر الرقمي يمر حاليا بتغييرات بسبب استخدام التكنولوجيا في التعلم. تأخذ هذه الدراسة شكل البحث النوعي ، باستخدام التحليل الوصفي كطريقة للاختيار. وفقا لنتائج هذه الدراسة ، لا يزال وجود اللغة العربية موجودا في العصر الرقمي 4.0 ، وهناك تجديد في التعلم ، يليه إلحاح التعلم. في العصر الرقمي الحالي ، تعتبر اللغة العربية حيوية للغاية في دراسة المدرسة. للعصر الرقمي عواقب على تعلم اللغة العربية في المدارس الدينية، بما في ذلك استخدام التكنولوجيا في التعلم، وتكييف المناهج الدراسية، وتنمية المهارات الرقمية، وتوفير مواد تعلم اللغة العربية.